Pengaruh Dosis Pupuk NPK dan Konsentrasi ZPT Giberelin Terhadap Pertumbuhan dan Hasil Tanaman Mentimun (Cucumis sativus L.) - Nining Anggraini; Nova Triani; Puji Lestari Tarigan (Jurnal Galung Tropika, 2025)
Cucumber (Cucumis sativus L.) is a vegetable from the Curcubitaceae family or gourds that originated in India and has spread throughout the world including Indonesia. In Indonesia, cucumber is one of the vegetables that is much favored by all levels of society because it can be consumed and used as a cosmetic and medicinal ingredient. This study aims to determine the effect of gibberellin concentration and NPK fertilizer dosage on the growth and yield of cucumber plants. The research was conducted in Dasri Village, Tegalsari District, Banyuwangi Regency, East Java,  from August to November 2024. This research was conducted using the method of Divided Plots Design (RPT) with two treatment factors. The treatments used were concentration of gibberellin as main plot and dosage of NPK fertilizer as sub plot. The concentration of gibberellin consisted of four levels, namely: 0 ppm/plant, 100 ppm/plant, 200 ppm/plant and 300 ppm/plant. The second factor is the dose of NPK fertilizer including: 100 kg/ha, 400 kg/ha, 500 kg/ha and 600 kg/ha. The results showed that the treatment combination of gibberellin concentration of 300 ppm/plant with NPK fertilizer dosage of 600 kg/ha affected to length of plant and total of leaves.